Rivaroxaban attenuates valvular inflammation and tissue remodeling in patients with severe aortic stenosis. (14th October 2021) - Kopytek, M; Zabczyk, M; Undas, A; Natorska, J
Abstract: Background: It has been demonstrated in a mouse model of atherosclerosis that non-vitamin K antagonist oral anticoagulants (NOACs) attenuate atherosclerotic plaque progression. However, it is not known whether NOACs can inhibit aortic stenosis (AS) progression. Aims: To evaluate whether rivaroxaban at therapeutic concentrations can impair valvular inflammation and valve remodeling in patients with severe AS. Methods: We recruited 38 patients with isolated severe AS aged 68±8 years (mean gradient 54 mmHg, max gradient 86 mmHg), including 18 individuals with AS and atrial fibrillation taking rivaroxaban (20 mg/daily for at least 3 years). Stenotic aortic valves were obtained during valve replacement surgery. Valvular expression of NFκB, matrix metalloproteinase 9 (MMP-9) and bone morphogenetic protein 2 (BMP-2) was evaluated by immunostaining. Primary cultures of valve interstitial cells (VICs) obtained from stenotic aortic valves were stimulated with TNF-α to induce inflammation. In parallel, VICs were cultured with TNF-α and rivaroxaban at therapeutic concentrations (1 and 10 μg/ml, corresponding to about 2.5 mg and 25 mg daily in vivo). The expression of NFκB, interleukin 1β (IL-1β), reactive oxygen species (ROS), MMP-9 and BMP-2 in VICs was assessed. The control VICs were cultured without any additives. All VICs were cultured for 72 hours and experiments were repeated 3 times. The fluorescence intensity was computed as the ratio (%) of positively and negatively stained areas. Results: We observed decreased valvular expression of NFκB (−54%), MMP-9 (−32%) and BMP-2 (−23%) in patients taking rivaroxaban compared to those without such treatment. TNF-α stimulation up-regulated expression of NFκB, IL-1β and ROS (+58%; +34%; +38%; all p<0.01) accompanied by higher expression of MMP-9 and BMP-2 (+49% for MMP-9 and +32% for BMP-2; both p<0.01), when compared to control cells. Rivaroxaban at a concentration of 10 μg/ml decreased the expression of ROS (−31%, p<0.01), inflammatory markers (NFκB −47% and IL-1β −22%, both p<0.01) and MMP-9 (−39%, p<0.01) compared to VICs cultured without rivaroxaban. Similarly, BMP-2 expression was down regulated after 10 μg/ml of rivaroxaban (−26%, p<0.01). Even low dose of rivaroxaban decreased VICs expression of NFκB, IL-1β and ROS by 38%, 18% and 25%, respectively (all p<0.01) as compared to cells stimulated with TNF-α only. Comparable effect was observed for MMP-9 and BMP-2 expression (−33%; −22%; both p<0.01). Conclusions: Rivaroxaban can decrease valvular inflammation and its remodelling and significantly inhibits inflammation, extracellular matrix activity and calcification of VICs. Our study suggests that NOACs, even at a low dose, could slow the rate of AS progression, at least in AS patients with mild-to-moderate AS and indications for anticoagulant therapy. Clinical relevance of these findings requires further studies. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Centre (NCN)